2021
DOI: 10.3855/jidc.14972
|View full text |Cite
|
Sign up to set email alerts
|

A straightforward molecular strategy to retrospectively investigate the spread of SARS-CoV-2 VOC202012/01 B.1.1.7 variant

Abstract: The spread of new SARS-CoV-2 variants represents a serious threat worldwide, thus rapid and cost-effective methods are required for their identification. Since November 2020, the TaqPath COVID-19 assay (Thermo Fisher Scientific) has been used to identify viral strains of the new lineage B.1.1.7, since it fails to detect the S-gene with the ∆69/70 deletion. Here, we proposed S-gene mutations screening with the Allplex SARS-CoV-2 assay (Seegene), another widely used RT-PCR test that targets Sarbecovirus E, SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…In the Allplex assay, mutations in the VOC B.1.1.7 variant in the S- and RdRP- gene targets did not affect the amplification curve pattern compared with the N gene. A study comparing amplification curve patterns of the envelope (E), N, and RdRP/S genes of the Allplex SARS-CoV-2 assay (Seegene) found peculiar, non-sigmoidal amplification curves in the RdRP/S genes that were associated with B.1.1.7 variant strains ( Ibba et al, 2021 ). Although the Allplex assay used the S-gene target, the Allplex SARS-CoV-2 assay used a combination of two gene targets: RdRP and the S gene.…”
Section: Discussionmentioning
confidence: 99%
“…In the Allplex assay, mutations in the VOC B.1.1.7 variant in the S- and RdRP- gene targets did not affect the amplification curve pattern compared with the N gene. A study comparing amplification curve patterns of the envelope (E), N, and RdRP/S genes of the Allplex SARS-CoV-2 assay (Seegene) found peculiar, non-sigmoidal amplification curves in the RdRP/S genes that were associated with B.1.1.7 variant strains ( Ibba et al, 2021 ). Although the Allplex assay used the S-gene target, the Allplex SARS-CoV-2 assay used a combination of two gene targets: RdRP and the S gene.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that the B.1.1.7 lineage rapidly spread becoming the prevalent lineage from January to March 2021. Indeed, a progressive increase in positive cases of SARS-CoV-2 infections and the concomitant emergence of the Alpha variant were reported in diverse regions of Italy [ 6 , 7 , 15 , 16 ]. Lai and colleagues reported that the B.1.1.7 lineage significantly increased from 3.5% in December 2020 to 86.7% in March 2021, replacing the previously circulating variant B.1.177 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation identified so far only in the SARS-CoV-2 variant that emerged in the UK (lineage B.1.1.7). Consequence of deletion of 21,765–21770 genome region, it is characterized by the two amino acids deletion at positions 69/70 (del69-70/(ΔH69/V70), and appears to have arisen in multiple genetic backgrounds of SARS-CoV-2, accordingly with some studies ( Ibba et al, 2021 ; Borges et al, 2021 ).…”
Section: Introductionmentioning
confidence: 90%